An 18-Month Epidemiologic Survey of 3364 Deceased COVID-19 Cases; a Retrospective Cross-sectional Study - Tavakolian, Ayoub; Ashrafi Shahri, Seyed Hassan; Jafari, Mohammad Ali; Pishbin, Elham; Zamani Moghaddam, Hamid; Foroughian, Mahdi; Reihani, Hamidreza (Archives of Academic Emergency Medicine, 2022)
Introduction: The COVID-19 pandemic has been considered an international problem. This study aimed to survey the demographic and clinical characteristics of the deceased COVID-19 patients. Methods: The present cross-sectional study was performed on all deceased COVID-19 patients who died in Imam Reza Hospital, Mashhad, Iran, from March 20, 2020, to September 23, 2021. Their data, including age, gender, complaints, and clinical symptoms at the time of admission, as well as information at the time of death (hour, shift, holiday/non-holiday) were analyzed and reported. Results: 3364 deaths due to COVID-19 have been registered during the study period (60.46% male). The patients' mean age was 66.99±16.97 (range: 1-101) years (92.7% of them were Iranian). The mortality at night shifts was less than day shifts (1643 vs. 1721). The average amount of deaths/day on holidays and workdays was (5.63 vs. 6.24). The number of deaths varied during the various hours of the day and night. Diabetes and cardiovascular diseases were the most common confounding factors, which were observed in 22.44% and 15.36% of the cases, respectively. Conclusion: Based on the findings of this series, COVID-19 mortality was frequently observed in male patients, those with the mean age of 66.99 years, morning shifts, and workdays.